Using Concept Maps to Create Meaningful Learning in Medical Education - Barbara J. Daley; Steven J. Durning; Dario M. Torre (MedEdPublish, 2016)
After defining concept maps, we will present the historical development and theoretical foundations of concept maps derived from disciplines outside of medical education. With this foundation and based on the scoping review conducted, the major focus of this article will shift to the application of concept mapping in medical education. We have selected instructional strategies and sample maps for three contemporary challenges facing medical education to illustrate the portability and broad application of concept maps: 1. linking basic sciences and clinical practice, 2. developing clinical reasoning, and, 3. interprofessional and group learning. Finally, future research studies in concept mapping are suggested.